MAKING A RESERVATIONSYSTEM USING SOFTWARE TENNIS VISUAL DBASE 7.0 - Abi Teguh Setiawan; Sahni D.P, SKom, MM Sahni D.P, SKom, MM (Jurnal Sistem Informasi, 2003)
Booking system is done conventionally by using records to create a schedule and a list of buyer. In this tennis court reservation system, the things most important is data accuracy and speed of customer service become the main priority.Speed of service is closely linked to efforts to improve the reservation system to run optimally, and may contribute positively to the company. One of them by applying it with a computerized reservation system to the human factor and the delay constraints are not accurate calculations can be immediately handled carefully.